Optimasi Jalur Distribusi dengan Metode Vehicle Routing Problem (VRP) - Agung Chandra; Bambang Setiawan (Institut Transportasi dan Logistik Trisakti, 2018)
The purpose of the study was to apply the method of Vehicle Routing Problem (VRP) Method to accelerate product distribution and minimize the use of fuel. The method of VRP is one of the solutions to find the shortest route from 57 locations in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi), four locations in Bandung, and three locations in Surabaya. The result shows that the most efficient method of VRP is by combining the heuristics and meta-heuristics – simulated annealing methods which reduce the distance about 11.79 % in Jabodetabek, 0 % in Bandung, and 8.98 % in Surabaya.